2017
DOI: 10.1002/cmdc.201600545
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel 2‐Aminonicotinamide Derivatives as Antifungal Agents

Abstract: Based on the structures of the reported compounds G884 [N-(3-(pentan-2-yloxy)phenyl)nicotinamide], E1210 [3-(3-(4-((pyridin-2-yloxy)methyl)benzyl)isoxazol-5-yl)pyridin-2-amine], and 10 b [2-amino-N-((5-(3-fluorophenoxy)thiophen-2-yl)methyl)nicotinamide], which inhibit the biosynthesis of glycosylphosphatidylinositol (GPI)-anchored proteins in fungi, a series of novel 2-aminonicotinamide derivatives were designed, synthesized, and evaluated for in vitro antifungal activity. Most of these compounds were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Recently, more members of this class of compounds were synthesized and shown to have bioactivity against a variety of fungi, including C. albicans , C. parapsilosis , C. glabrata , and Cryptococcus neoformans . Selected members of this group used against C. albicans caused destruction of the mannoprotein coat, consistent with inhibition of the biosynthesis of GPI anchor proteins ( 48 ). The two pyridine amide compounds tested here were found to generate very similar profiles, strongly supporting the hypothesis that the two molecules target the same cellular process.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Recently, more members of this class of compounds were synthesized and shown to have bioactivity against a variety of fungi, including C. albicans , C. parapsilosis , C. glabrata , and Cryptococcus neoformans . Selected members of this group used against C. albicans caused destruction of the mannoprotein coat, consistent with inhibition of the biosynthesis of GPI anchor proteins ( 48 ). The two pyridine amide compounds tested here were found to generate very similar profiles, strongly supporting the hypothesis that the two molecules target the same cellular process.…”
Section: Discussionmentioning
confidence: 79%
“…The Nakamoto group reported that the pyridine amide 10b ( 45 ) and the 2-aminopyridine E1210 ( 46 ) inhibited the function of the Gwt1 protein in the GPI biosynthetic pathway and exhibited good bioactivity against Candida albicans ( 47 ) and Aspergillus fumigatus . A series of analogs of compounds 10b and E1210 have been synthesized and were found to display broad-spectrum antifungal activity and even to inhibit fluconazole-resistant Candida albicans ( 48 ). Two compounds (from Yan Li and Dazhi Zhang) of this family (GPI-C107 and GPI-LY7) were tested with the GRACE 1.0 collection to identify possible sensitive and resistant strains; both compounds had very similar profiles but were clearly distinct from the azoles, the echinocandins, and amphotericin B.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, our group designed and synthesized a series of novel 2-aminonicotinamide derivatives and reported that compound 11g (Figure 1) is a promising new antifungal agent with potent and broad-spectrum antifungal activity in vitro (Ni et al, 2017). Here, in order to expand the antifungal spectrum of 11g, we investigated the antifungal activity of 11g against 17 clinical isolates of Candida species.…”
Section: Mic 80 Of 11g In Vitromentioning
confidence: 99%
“…To date, several GPI biosynthesis inhibitors, such as BIQ, G884, 10b, and E1210, etc., have been synthetized and regarded as new antifungal agents (Supplementary Figure S1; Tsukahara et al, 2003;Nakamoto et al, 2010;Miyazaki et al, 2011;Mann et al, 2015). In the course of optimizing these compound structures, we designed and synthetized a 2-aminonicotinamide derivative named 11g (Ni et al, 2017). In 2017, our group reported that 11g could decrease the GPI content in the C. albicans cell wall (Ni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation